Ligamentum arteriosum: Muscular and contractile - Mensah, Benedicta; Justus Liebig University Giessen (My University, 2023)
Ductus arteriosus is a muscular artery in fetal circulation, spanning from the bifurcation of the pulmonary trunk to the aortic arch, shunting blood directly from pulmonary circulation into systemic circulation thus by-passing the fluid-filled lungs. Postnatally, it changes name to the ligamentum arteriosum (LA), when a cascade of anatomical and physiological processes leads to its closure. Though the LA has generally been considered as a fibrosed remnant of the ductus arteriosus, anecdotal and contradictory reports still describe the LA as a small muscular artery. We hypothesized the likelihood of contractile muscular elements retainment in this so-called ligament. To investigate this, mediastinum of wild-type mouse, pig, and human LA were subjected to routine and special histological staining, single-immunolabeling, electron microscopy (mouse and pig only), and tension recording of explanted pig LA in organ bath experiments. Contrary to a canonical ligament, the LA was mainly made up of α-smooth muscle actin-positive cells in all three species, confirmed by routine and special histological staining as well as transmission electron microscopy. Myocytes within the LA contracted in response to exogenous noradrenalin (NA). NA-induced precontracted LA relaxed upon administration of the α1-adrenergic blockers (prazosin and tamsulosin). Though the LA does not function in its original capacity as fetal shunt, it is clearly not a passive structure, and may be described as muscular and contractile. The contractile abilities of LA myocytes may act on the two great vessels to which it is attached causing a change in their distensibility.
Keywords: ddc:610